UPAYA ADMINISTRATIF DALAM SENGKETA KEPEGAWAIAN: (Analisis Putusan PTUN Makassar Nomor 122/G/2019/PTUN.Mks) - Kadir, Muhammad Zulfadli; Akmal, Andi Muhammad (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
The aim of this research is to describe the Decision of the State Administrative Court Number 122/G/2019/Ptun.Mks concerning Employment Disputes regarding judges’ considerations in administrative efforts when resolving disputes at the State Administrative Court. The problem raised in this research is how the judge considers the administrative efforts taken by the Plaintiff in the exception contained in decision Number 122/G/2019/Ptun.Mks. This research is field research using qualitative analysis with a normative syar’i and empirical juridical approach. Data collection methods were carried out by means of interviews, observation and documentation. The results of this research indicate that the administrative efforts taken by the Plaintiff before filing the lawsuit at the Makassar State Administrative Court were procedurally appropriate due to the Mayor’s failure to respond to administrative efforts in the form of objections submitted by the Plaintiff and then the Mayor did not provide a response or answer in writing.